NILAI PENDIDIKAN ISLAM DALAM ADAT PERNIKAHAN MASYARAKAT MELAYU SAMBAS DI DESA SARANG BURUNG DANAU KECAMATAN JAWAI KABUPATEN SAMBAS - Marisa Marisa (Tarbiya Islamica, 2014)
The purpose of this study is to reveal about the implementation of the Sambas Malay traditional wedding ceremony in the Sarang Burung Danau Village, Jawai District, Sambas Regency and the values ​​of Islamic education in the Sambas Malay wedding customs, Jawai District, Sambas Regency. This research is a descriptive type with a qualitative approach. Data was collected by using interview techniques, observation and documentation techniques. Researchers themselves, assisted by interview and observation guidelines. The data analysis technique used is data collection, data reduction, data presentation and conclusion drawing. The results of the research that have been obtained are the implementation of the Sambas Malay traditional wedding ceremony in the Sarang Burung Danau Village, Jawai District, Sambas Regency, namely the ceremony before the wedding, the implementation of the wedding and after the wedding. The values ​​of Islamic education in the Malay marriage custom of Sambas in the Sarang Burung Danau Village, Jawai District, Sambas Regency are the Islamic educational values ​​contained in the marriage custom, the i'tiqodiyah educational values ​​such as application, cikram, marriage contract which contains which in religion In Islam, before marriage, the prospective partner is held ta'aruf, proposal or sermon and then married. The existence of the value of muamalah in which people work together to relieve the host and make the wedding party a success, where this value is contained in Islam. As for the value of khuluqiyah education, which is in the stage of returning home, there are educating advices for the bride and groom in which the husband and wife carry out their duties properly, for example providing physical and spiritual support, then for biological parents and parents-in-law to provide a good example or role model for the bride and groom. their newly married child.